Interfaith friendships among emerging adulthood in Surabaya: The role of tolerance and stigma consciousness - Nicolas Valentino Fonda; Darmawan Muttaqin (HUMANITAS published by Universitas Ahmad Dahlan., 2023)
Forming quality interfaith friendships is not impossible. Additionally, our society has become accustomed to differences. However, a clear explanation for the difficulty of forming such friendships has yet to be established. This study aimed to investigate the influence of tolerance and stigma consciousness on the quality of interfaith friendships. The research involved 400 respondents aged 18-25, comprising 200 Muslim respondents with at least one non-Muslim friend and 200 non-Muslim respondents with at least one Muslim friend. The quality of friendship was evaluated using the McGill Friendship Questionnaire (MFQ), while tolerance and stigma consciousness were measured using the Tolerance Index Questionnaire (TI) and Stigma Consciousness Questionnaire (SCQ), respectively. Multiple regression analysis was utilized to test the research hypothesis. The study results indicate that tolerance and stigma consciousness are significant factors in determining the quality of interfaith friendships. Individuals with tolerance and low levels of stigma consciousness are more likely to form quality interfaith friendships.